Water and nitrogen regulation strategy for wolfberry farmland based on nitrogen balance in the Yellow River irrigation districts of Gansu Province, China - Yin, Minhua; Tian, Rongrong; Ling, Yi; Yang, Yuqing; Ma, Yanlin; Kang, Yanxia; Qi, Guangping; Wang, Jinghai (Frontiers in Plant Science, 2025)
Agricultural production frequently encounters challenges, including soil nitrogen pollution and imbalances resulting from improper irrigation and fertilization practices. This study focuses on wolfberry farmland, analyzing the effects of four irrigation levels [full irrigation (W0, 75%−85% θf), mild water deficit (W1, 65%−75% θf), moderate water deficit (W2, 55%−65% θf), and severe water deficit (W3, 45%−55% θf)] and four nitrogen application levels [no nitrogen application (N0, 0 kg·ha−1), low nitrogen application (N1, 150 kg·ha−1), medium nitrogen application (N2, 300 kg·ha−1), and high nitrogen application (N3, 450 kg·ha−1)] on nitrogen uptake by wolfberry plants, soil nitrogen loss, plant-soil nitrogen balance, and nitrogen use efficiency. The results indicate that: (1) Plant dry matter yield (1338.90−2893.52 kg·ha−1), fruit yield (1368.19−2623.09 kg·ha−1), plant nitrogen uptake (28.32−96.89 kg·ha−1) and fruit nitrogen uptake (23.53−63.56 kg·ha−1) all increased with higher irrigation and nitrogen application levels, following the trend W1 > W0 > W2 > W3 and N2 > N3 > N1 > N0. Compared with the other treatments, W1N2 treatment increased by 4.37%−116.11%, 6.36%−91.72%, 15.23%−242.16% and 10.86%−170.13%, respectively. (2) Soil NO3−–N content initially decreased, then increased, and ultimately decreased again with increasing soil depth, demonstrating inconsistent trends in response to changes in irrigation and nitrogen application. The highest residual soil NO3−–N at the end of the wolfberry growth period was recorded in the W0N3 treatment, measuring 186.17 kg·ha−1. In contrast, the lowest level was observed under the W3N0 treatment at 90.13 kg·ha−1, which was reduced by 12.25%−51.59% compared with other treatments. (3) The soil N2O flux (28.50–433.41 ug·m−2·h−1) and total emissions (0.40–1.67 kg·ha−1) increased with increased irrigation and nitrogen application. (4) The W1N1 treatment showed the highest nitrogen productivity (14.29 kg·kg−1), absorption efficiency (0.85 kg·kg−1), and recovery efficiency (27.14%), outperformed other treatments by 0.64–10.94 kg·kg−1, 0.10−0.65 kg·kg−1, and 2.52–18.80%, respectively. Overall, a combination of 392.40 mm of irrigation and 150 kg·ha−1 of nitrogen represented the optimal strategy for efficient and sustainable wolfberry production in the Yellow River irrigation districts of Gansu and similar regions.